Kesaksian Testimonium de Auditu dalam Kajian Hukum Pidana Islam - Alwi Sihab Siregar; Zulpahmi Lubis (IAIN Langsa, 2026)
This study aims to analyze the position, probative value, and relevance of testimonium de auditu within the framework of Islamic criminal law, while also examining it in comparison with positive criminal law. This research employs a qualitative library-based methodology using a normative juridical approach, enriched by conceptual and comparative approaches. Data are analyzed through content analysis and critical discourse analysis of fiqh jinayah literature, usul al-fiqh, and contemporary scholarly works. The findings indicate that testimonium de auditu does not possess the authority of a primary evidentiary instrument in Islamic criminal law; nevertheless, it may be conditionally accepted as supporting information through the concepts of istifadah and maslahah. These findings underscore the normative flexibility of Islamic criminal law in responding to the complexities of modern evidentiary practices while maintaining principles of prudence and substantive justice.